Foot-and-Mouth Disease Virus - SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2005)
The chapters in this volume provide an account of the present knowledge and understanding of Foot and Mouth disease virus pathogenesis and global epidemiology, the detailed structure of the virus itself and the properties of its RNA genome. Also considered are the immune response of the host and the state of the art in vaccine production, and the nature of virus evolution. It is clear that in all these areas there is still much more to learn about this fascinating virus. Because of its highly contagious nature research work on FMDV is restricted to a small number of laboratories worldwide that have adequate containment facilities. Despite this restriction, the recent progress in research on FMDV which is described in this volume has provided a remarkable level of understanding of this unique virus.
and History of Foot-and-Mouth Disease Virus -- Foot-and-Mouth Disease: Host Range and Pathogenesis -- Translation and Replication of FMDV RNA -- The Structure of Foot-and-Mouth Disease Virus -- Natural and Vaccine Induced Immunity to FMD -- Global Epidemiology and Prospects for Control of Foot-and-Mouth Disease -- Foot-and-Mouth Disease Virus Evolution: Exploring Pathways Towards Virus Extinction.
Keywords: Virology; Virology